Comparison of the efficiency of cleaning and disinfection protocols for hand endodontic instruments - Jovanović-Medojević, Milica; Opačić Galić, Vanja; Geler, Katarina; Pavlica, Dušan (Vojnosanitetski pregled, 2023)
Background/Aim. There is no standard protocol for cleaning and disinfection of used endodontic instruments before their sterilization and reuse. The aim of this study was to determine the efficiency of the different methods of removing biological debris from different types of used hand stainless steel endodontic instruments. Methods. A total of 120 hand stainless steel endodontic instruments: KerrTM reamers, KerrTM files, and HedströmTM files, each forty ISO 25, used for root canal treatment on extracted teeth, were analyzed. The used instruments were divided into four groups based on different decontamination protocols. The evaluation of the efficiency of the cleaning methods was based on the evaluation of the amount of stained organic residues on the instruments (Van Gieson staining). Samples were analyzed by stereomicroscopy (x40). Statistical analysis was performed using the Mann-Whitney U test for the KerrTM reamers and HedströmTM files, while the One-Way ANOVA/Bonferroni test was used for the KerrTM files, at a significance level of 5% (α = 0.05). Results. Residual biological debris was observed on 93.3% of all the samples taken. The thermal disinfectant cleaning method showed the lowest contamination values ​​for all types of instruments. The method of mechanical cleaning showed that the mean value of maximum biologic contamination (MBC) was 58.5% for the KerrTM reamers and 56.2% for KerrTM files, while for HedströmTM files, the highest MBC (50.2%) was shown by the ultrasonic method of cleaning. Conclusion. The use of a thermal disinfectant was the most efficient cleaning method for all three types of hand endodontic instruments.
Keywords: decontamination; dental instruments; endodontics; infection control; root canal preparation